A Website-Based Digital Cashier System for Bakery Shops with Real-Time Transaction and Reporting Features - Putri Alfa Hidayah; Muhammad Ihsan; Zulhipni Reno Saputra Elsi (Universitas Islam Kuantan Singingi, 2025)
The bakery business as one of the fast-growing small and medium enterprises (SMEs) sector needs technological solutions that are able to meet the needs of fast and accurate transactions. The researcher found problems with the cashier system in the bakery where it still often uses conventional transactions due to various obstacles, such as limitations in recording transactions, difficulties in monitoring stock in real time, and a long-time reporting process. This condition can hinder productivity and timely decision-making. This research aims to develop a website-based digital cashier system, bakery businesses can optimize their operations through integrated features. The method used in designing the system is Waterfall, which includes the stages of needs analysis, One of the important features is real-time transactions, which allow the cashier to record sales directly and synchronize the data to the server. In addition, the real-time report feature makes it easier for bakery business owners to monitor business performance instantly, without having to wait for a manual recapitulation process. A web-based digital cashier system for bakeries is a relevant and strategic solution because it can provide added value to bakery business management, both in terms of operational efficiency and increased customer satisfaction. By utilizing this technology, it is hoped that bakeries can compete more effectively in an increasingly competitive market